Síntese, reatividade e atividade antimicrobiana de β-enamino ésteres α-clorados utilizando K-10 e irradiação de microondas - Oriques, Daniela Alves (2005)
Enamino carbonylic compounds are important synthetic intermediates used in the synthesis of heterocycles and natural products. Our group of research has been dedicating much of our efforts to the development and implementation of simple and efficient methodologies to obtain β-enamino carbonylic compounds, mainly due to their functionality and ability to react both as ambident nucleophiles and as ambident electrophiles. In this dissertation, we study the synthesis and reactivity of new α-chloro functionalized N-substituted β-enamino acyclic compounds. In the synthesis of α-chlorinated β-enamino esters (2a-g) was employed the condensation of ethyl 2-chloro-acetoacetate with primary amines. This convenient and safe procedure uses the clean chemistry methodology of microwave-assisted solid support (K-10) synthesis in the absence of solvent. The reactivity and regiochemistry of the α-chlorinated β-enamino compounds was assessed through the study of cyclization reactions involving the coupling of these substrates with dinucleophiles such as hydrazine and semicarbazide derivatives. The obtained heterocycles showed the influence of the chloro substituent at the α position, which led to the inversion of reactivity of this center, allowing the preparation of heterocyclic compounds having four and six members. These functionalized heterocycle derivatives are attractive targets for the discovery of new active molecules as they have high potential to present a broad range of biological properties. Therefore, evaluation of the antimicrobial activity of the newly synthesized compounds was carried out using the in vitro Bioautography assay.